Economies of scale and scope in Australian telecommunications - Bloch, Harry; Madden, Gary; Savage, Scott (Springer Science + Business Media B.V., Formerly Kluwer Academic Publishers B.V., 2001)
This paper employs a composite cost function to examine the cost structure of Australian telephoneservices. The composite cost model combines thelog-quadratic input price structure of the translogmodel with a quadratic structure for multiple outputs. Quadratic output structures permit the measurement of economies of scale, economies of scope, and subadditivity without prejudging their presence. Model estimates, on Telstra system data from 1926 to1991, show that the production of Australian telephoneservices exhibits economies of scope but no rayeconomies of scale.